Two-stage optimization of hydrogen and storage coordination for a multi-region flexible intermodal multi-energy port system - Xu, Yueyang; Fu, Haijun; Yang, Junru; Zhao, Leyuan; Zhang, Yang (Frontiers in Energy Research, 2024)
To address the issue of imbalanced electricity and hydrogen supply and demand in the flexible multi-energy port area system, a multi-regional operational optimization and energy storage capacity allocation strategy considering the working status of flexible multi-status switches is proposed. Firstly, based on the characteristics of the port area system, models for system operating costs, generation equipment, energy storage devices, flexible multi-status switches, and others are established. Secondly, the system is subjected to a first-stage optimization, where different regions are optimized individually. The working periods of flexible multi-status switches are determined based on the results of this first-stage optimization, targeting the minimization of the overall daily operating costs while ensuring 100% integration of renewable energy in periods with electricity supply-demand imbalances. Subsequently, additional constraints are imposed based on the results of the first-stage optimization to optimize the entire system, obtaining power allocation during system operation as well as power and capacity requirements for energy storage devices and flexible multi-status switches. Finally, the proposed approach is validated through simulation examples, demonstrating its advantages in terms of economic efficiency, reduced power and capacity requirements for energy storage devices, and carbon reduction.